THE INFLUENCE OF JOB SATISFACTION TOWARDS ORGANIZATIONAL COMMITMENT AT BENGKEL SAMARINDA, MEDAN - Javerson Simamora; Edward Harnjo; Eddy Gunawan; Sri Aprianti Tarigan; Susanto Susanto (Bajang Institute, 2022)
Nowadays, most of the companies focus on increasing the commitment of their employees toward the companies themselves through motivation programs and incentives without paying attention to other factors that play a role in increasing the commitment of the employees. In this research, the writer does a research on Bengkel Samarinda which is addressed at Gang Perjuangan No 42N, Titi Kuning, Medan, North Sumatra. Bengkel Samarinda is a workshop that produces furniture and house equipment made from metal. To calculate variable X (Job Satisfaction), the writer uses environmental factor and individual factor as the indicator and variable Y (Organizational Commitment), the writer uses role stress, empowerment, job insecurity and employability, and distribution of leadership as the indicator. In doing this research, the writer uses questionnaire filled with 9 questions and each question consists of 5 answers that can be chosen, and the questionnaire is distributed to 40 respondents. The coefficient of correlation (r) obtained in this research is 0.63, which means that there is a moderate positive relationship. To test the hypothesis, writer uses a valid validity test, reliable reliability test, correlation coefficient test that is found 0.63 representing that there is a significant relationship between each variable, the z-test that shows the z-count is 3.93, z-table is 1.96. This result shows that the z-count>z-table so the null hypothesis is rejected, the multiple regression with the equation y = -0.09 + 0.788x and coefficient of determination is 39.7. It means that job satisfaction only influences around 39.7% towards the organizational commitment. The rest of 60.3% would be affected by other factors.